Pengaruh Efektivitas, Akuntabilitas, Dan Transparansi Sekolah Terhadap Pengelolaan Dana Bantuan Operasional Sekolah (BOS): Studi kasus pada Sekolah Dasar di Kecamatan Simo dan Bendosari - Dava Pradana, Muhammad; Kristiyanti, LMS; Pardanawati, Sri Laksmi (Nur Science Institute, 2025)
This study aims to analyze the influence of effectiveness, accountability, and transparency on the management of School Operational Assistance (BOS) funds in elementary schools located in Simo and Bendosari Districts. A quantitative approach was employed with a saturated sampling technique involving 65 teachers and staff from six elementary schools. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that effectiveness, accountability, and transparency have a positive and significant impact on BOS fund management. These findings highlight that higher levels of effectiveness, accountability, and transparency in schools contribute to better financial management of BOS funds. The study provides practical implications for schools and local governments in enhancing financial governance to ensure that BOS funds are allocated appropriately and utilized optimally.